IInfografia como estratégia para ensino de leitura e de escrita de textos multimodais - Cláudia Ribeiro Rodrigues (2018)
The new tools of reading and writing from new technologies require subjects capable of articulating a multiplicity of semiosis, both as readers and as producers of texts, to construct the meaning of a statement. In addition to multimodalities, technologies have allowed a greater approximation between the diverse cultures that coexist in the contemporary world and this requires of the practical schools that contemplate the abilities to read and produce multimodal texts in a critical, ethical and democratic way, that is, a proposal of teaching to develop the multiliteracies. In this way, it is up to the teachers to work the multimodal texts that circulate socially so that the students acquire the skills necessary for their reading and their production in the school context and especially in the social context. In this sense, interdisciplinary literacy projects are a very effective resource, since, in addition to allowing the articulation between the knowledge, they offer a significant work focused on the development of reading and writing practices with a view to the social use of language. As a result, this dissertation was designed to develop an interdisciplinary literacy project aimed at expanding the reading and writing skills of multimodal texts based on the reading of infographics, a genre composed of several semiosis, widely used in materials and in various spheres of present-day society. This is an empirical research of a qualitative nature in education applied to a 9th grade class from Elementary School II of a municipal public school located in the city of Divinópolis/MG. The discussions are based on the presuppositions of the sociointeractionist teaching theory of the language that guides the official documents for the teaching of the Portuguese language anchoring in the perspective of the Dialogical Analysis of the Discourse Genres, of researchers linked to the Circle of Bakhtin (1992) of the Sociodiscursive Interactionism of Dolz and Schneuwly (2004) and collaborators. The theories of Dionisio (2011), Paiva (2016) and Ribeiro (2012, 2013, 2015, 2016) on reading and production of multimodal texts and infographics, as well as Rojo (2009, 2012, 2013) conceptions about multiliteracies and Kleiman (1999, 2007, 2014) on literacy projects and interdisciplinarity. As data collection instruments, we used the observations made during the lessons recorded in a field diary, the activities generated during the process, photos and audio and video recordings. The results indicate that systematic interdisciplinary work aimed at reading and producing infographics has contributed positively to the development of reading and multimodal text production skills and has made the teaching and learning process more meaningful for students and teachers.